1996
DOI: 10.1021/jp962046d
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Dynamics of a Protonated Retinal Schiff Base in Solution

Abstract: The dynamics of all-trans and 13-cis retinal protonated Schiff base (RPSB) were studied in different solvents by means of picosecond transient spectroscopy. The decay time of the excited state absorption was found to be wavelength dependent due to the contribution of the faster decay of stimulated emission. The stimulated emission has a lifetime of a 2.5−4 ps while the excited state absorption decay is biexponential with lifetimes of 2.5−4 and 10−12 ps. The fluorescence quantum yield is strongly temperature de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
186
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(208 citation statements)
references
References 30 publications
21
186
0
1
Order By: Relevance
“…However, this perturbation need not influence the quantum efficiency for photoisomerization. Indeed, mutations that alter the excited state lifetime by more than an order of magnitude were found to have a negligible impact on the quantum efficiency for photoisomerization (14,22). The role of the protein in mediating the all-trans to 13-cis photoisomerization appears be largely as a catalyst along the C 13 AC 14 bond and as an inhibitor along all other double bonds (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this perturbation need not influence the quantum efficiency for photoisomerization. Indeed, mutations that alter the excited state lifetime by more than an order of magnitude were found to have a negligible impact on the quantum efficiency for photoisomerization (14,22). The role of the protein in mediating the all-trans to 13-cis photoisomerization appears be largely as a catalyst along the C 13 AC 14 bond and as an inhibitor along all other double bonds (21).…”
Section: Discussionmentioning
confidence: 99%
“…An implication that emerged from some of the earlier work is that such a bias might facilitate rapid conversion to the 13-cis form and may even be necessary to achieve a high quantum yield for photoisomerization. On the other hand, recent studies of bR mutants revealed quantum efficiencies for photoisomerization that were remarkably constant and similar to the efficiency for native bR, despite excited-state lifetimes that varied by an order of magnitude (14,(20)(21)(22). This suggests that rapid conversion to the 13-cis form might not be necessary to attain a high quantum efficiency for photoisomerization.…”
mentioning
confidence: 92%
“…However, unlike ROHF/AS6 and AS?, there is no explicit barrier, and so the effect on the dynamics can be expected to be less dramatic than for those methods. There is experimental evidence that the excited-state decay of the full retinal chromophore, both in solution [41] and in the protein environment [42][43][44], is multi-exponential. The results in solution have been shown to arise from a barrier on the excited-state surface [41].…”
Section: Ab Initio Excited State Surface Scansmentioning
confidence: 99%
“…There is experimental evidence that the excited-state decay of the full retinal chromophore, both in solution [41] and in the protein environment [42][43][44], is multi-exponential. The results in solution have been shown to arise from a barrier on the excited-state surface [41]. It remains to be seen whether the OM2/GUGA-CI method can model this dynamics accurately, but the results for PSB3 suggest that this approach is promising.…”
Section: Ab Initio Excited State Surface Scansmentioning
confidence: 99%
“…In contrast, illumination of the all-trans chromophore in solution results in several photoproducts with 11-cis being the most dominant (6)(7)(8). The isomerization quantum yield is greater than 50% in proteins (23), but rarely exceeds 20% in solution (6)(7)(8)(9)(10). Finally, the time scale for isomerization in solution has been measured to be 10 ps (9), while it is faster than 2 ps in protein environments (24,25).…”
mentioning
confidence: 96%